Analisis Penerapan Metode Pembelajaran Problem Based Learning (PBL) Meningkatkan Pemahaman Siswa dalam Pelajaran Fisika - Ervinatus Tri Wulansari; Roifatul Masrusoh; Muhammad Hasan Muzammil; Singgih Bektiarso (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Classroom management is one of the important skills that a teacher must have to understand, analyze, make decisions, and take action to create a dynamic and conducive classroom atmosphere. Learning model planning is one of the indicators to support the success of a learning goal by analyzing student needs. For students, physics is a complicated lesson, often they avoid or fear this lesson. The Problem Based Learning (PBL) model is the most appropriate model to apply because this learning approach by implementing an authentic problem (real experience with what students often encounter or find in life) to students. This research is based on the literature review method by collecting data from various journals and previous scientific sources. The process in this method includes searching for literature relevant to the topic. The results show that physics learning using the PBL method shows very significant results, the PBL method students are able to understand concepts in depth compared to conventional learning or lectures.